2001
DOI: 10.1002/ajim.1040
|View full text |Cite
|
Sign up to set email alerts
|

Cohort mortality study of Philadelphia firefighters

Abstract: Our study found no significant increase in overall mortality among Philadelphia firefighters. However, we observed increased mortality for cancers of the colon and kidney, non-Hodgkin's lymphoma and multiple myeloma. There was insufficient follow-up since the introduction of diesel equipment to adequately assess risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2001
2001
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(95 citation statements)
references
References 27 publications
8
84
0
Order By: Relevance
“…In a later proportionate mortality study, Watanabe and Kang 262 reported similar findings for army (PMR 5 0.87, 95% CI: 0.61-1.20) and marine (PMR 5 0.51, 95% CI: 0.14-1.31) Vietnam veterans. Cancer incidence and mortality studies of firefighters reported excess risks for multiple myeloma 116,[263][264][265] however, the specific exposures likely to drive these associations we are not indicated.…”
Section: Other Occupational and Environmental Factorsmentioning
confidence: 87%
“…In a later proportionate mortality study, Watanabe and Kang 262 reported similar findings for army (PMR 5 0.87, 95% CI: 0.61-1.20) and marine (PMR 5 0.51, 95% CI: 0.14-1.31) Vietnam veterans. Cancer incidence and mortality studies of firefighters reported excess risks for multiple myeloma 116,[263][264][265] however, the specific exposures likely to drive these associations we are not indicated.…”
Section: Other Occupational and Environmental Factorsmentioning
confidence: 87%
“…However, international research conducted on this occupation showed that the suicide risk for fire fighters is actually lower than the general male population. 35,36 Only four suicide-prevention programs targeted people from culturally and linguistically diverse backgrounds. Migration has been considered a potential factor of stress, which may trigger mental health problems and suicidal behaviours.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, Hanson 1990 [5] suggested an association between firefighters and lung cancer, but it is a singular finding among 12 other studies that find no increase in risk for lung cancer among firefighters [6]- [17]. Another occupational group that may have substantive PAH exposure is asphalt laying workers.…”
mentioning
confidence: 93%